2012
DOI: 10.1371/journal.pone.0030453
|View full text |Cite
|
Sign up to set email alerts
|

RhoE Is Regulated by Cyclic AMP and Promotes Fusion of Human BeWo Choriocarcinoma Cells

Abstract: Fusion of placental villous cytotrophoblasts with the overlying syncytiotrophoblast is essential for the maintenance of successful pregnancy, and disturbances in this process have been implicated in pathological conditions such as pre-eclampsia and intra-uterine growth retardation. In this study we examined the role of the Rho GTPase family member RhoE in trophoblast differentiation and fusion using the BeWo choriocarcinoma cell line, a model of villous cytotrophoblast fusion. Treatment of BeWo cells with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…In an in vitro model of villous cytotrophoblast fusion, Collett et al treated BeWo choriocarcinoma cells with a cell permeable cyclic AMP analogue, dibutyryl cyclic AMP (dbcAMP). As a result, there was a strong upregulation of Rnd3 24h after dbcAMP treatment, coinciding with the observation of the onset of cell fusion (28). Liebig with colleagues (77) also observed that RND3 protein levels were specifically and transiently upregulated upon basal keratinocyte differentiation, while RND3 depletion induced hyperproliferation and delayed initiation of keratinocyte differentiation.…”
Section: Physiological Function Of Rnd3supporting
confidence: 67%
“…In an in vitro model of villous cytotrophoblast fusion, Collett et al treated BeWo choriocarcinoma cells with a cell permeable cyclic AMP analogue, dibutyryl cyclic AMP (dbcAMP). As a result, there was a strong upregulation of Rnd3 24h after dbcAMP treatment, coinciding with the observation of the onset of cell fusion (28). Liebig with colleagues (77) also observed that RND3 protein levels were specifically and transiently upregulated upon basal keratinocyte differentiation, while RND3 depletion induced hyperproliferation and delayed initiation of keratinocyte differentiation.…”
Section: Physiological Function Of Rnd3supporting
confidence: 67%
“…The significance of the cAMP/PKA signaling pathway has been proven in regulating the transcription and post-translational acetylation, dephosphorylation and desumoylation of glial cells missing-1 (GCM1), which subsequently regulates syncytin expression and controls human trophoblast cell differentiation along the syncytialization pathway as the master transcription factor [43,44,54e56]. Moreover, the cAMP/PKA pathway also regulates transcriptional activities of many genes in the human trophoblast fusogenic machinery, including CYP17 [57], old astrocyte specifically induced substance (OASIS) [43], human placental growth factor (PlGF) [58] and the Rho GTPase family member RhoE [45], as well as the production and secretion of hCG [43,59] and progesterone [60] by the syncytiotrophoblast.…”
Section: Discussionmentioning
confidence: 99%
“…Several signaling pathways have been reported to be involved during trophoblast cell fusion, including PKA [43][44][45], ERK1/2 [43,46] and p38 MAPK [43,46,47] pathways. To identify upstream signaling pathways that drive the upregulation of furin during FSKinduced fusion of BeWo cells, different inhibitors of these signaling pathways were administrated upon FSK treatment.…”
Section: Furin Expression Is Stimulated By Camp-pka Signaling Pathwaymentioning
confidence: 99%
“…CBP‐GCMa complex, in turn, leads to transactivation of fusogenic protein syncytin‐1 . There are further evidences that suggest the role of RhoE, a member of Rho GTPase family in trophoblast fusion downstream of cAMP/PKA signaling (Fig. ).…”
Section: Signaling Pathways Involved During Syncytialization Of Trophmentioning
confidence: 92%